The dynamic of psycho-emotional condition in patients with chronic HCV infection (F1-F3) treated with bicyclol - K. V. Kozlov; R. M. Mukhtarov; K. V. Zhdanov; V. S. Sukachev; A. V. Saulevich; Yu. I. Lyashenko; Yu. I. Bulankov (Журнал инфектологии)
Purpose of the study. To evaluate the psycho-emotional state in patients with chronic viral hepatitis C before and after treatment with bicyclol.Materials and methods. The study included 124 male patients with chronic hepatitis C aged 20 to 52 years (average 34.7 ± 6.5). The patients were randomized into 2 groups: group I, including 83 patients with mild to moderate liver fibrosis (F1-2 according to METAVIR); and group II – 41 patients with severe liver fibrosis (F3 according to METAVIR). After antiviral therapy with direct antiviral agents, patients in each group were divided into 2 subgroups: an experimental group, which was prescribed the bicyclol to potentiate the anti-inflammatory effect, and a control group – without pathogenetic therapy. The psycho-emotional state was evaluated using the “Well-being, activity, mood” methodology.Results. As a result of complex etiopathogenetic therapy, a decrease in liver stiffness was observed in both patients with moderate and severe liver fibrosis. In patients of the experimental subgroup with moderate liver fibrosis, a decrease in liver density was observed from 7.10 kPa [6.70; 8.70] to 5.80 kPa [5.60; 7.00] (p = 0.008), and in the control subgroup – up to 6.40 kPa [5.80; 7.40] (p = 0.03), while in the experimental subgroup the decrease in liver density was significantly more pronounced (p = 0.04). When taking the questionnaire “Well-being, activity, mood” by patients with mild and moderate liver fibrosis before starting antiviral therapy, the final scores were in the normal range: total score 5.77 [5.53; 6.03], “well-being” indicator 5.80 [5.60; 6.20], “activity” indicator 5.30 [5.00; 5.60], “mood” indicator 6.10 [6.00; 6.20]. At the same time, patients with severe fibrosis had statistically significantly lower results for the studied indicators (p<0.001): total score 5.13 [4.90; 5.30], “well-being” 4.60 [4.50; 5.30], “activity” 5.20 [5.10; 5.50], “mood” 5.40 [5.20; 5.50], while the “well-being” indicator was below normal. After etiopathogenetic therapy, there was an improvement in the results of the “Well-being, activity, mood” method (p<0.05) both in the group with mild and moderate, and in the group with severe liver fibrosis, while in the control subgroups the severity of the observed changes was significantly lower (p<0.05).Conclusion. The use of bicyclol after antiviral therapy in patients with pre-cirrhotic liver fibrosis due to chronic hepatitis C led to a statistically significant decrease in liver stiffness, contributed to an improvement in the psycho-emotional state and was accompanied by a decrease in the activity of alanine aminotransferase, aspartate aminotransferase, an increase in the number of platelets and fibrinogen in the blood serum.